2013
DOI: 10.1038/nsmb.2706
|View full text |Cite
|
Sign up to set email alerts
|

Multisite phosphorylation networks as signal processors for Cdk1

Abstract: The order and timing of cell cycle events is controlled by changing substrate specificity and different activity thresholds of cyclin-dependent kinases (CDK). However, it is not understood how a single protein kinase can trigger hundreds of switches in a sufficiently time-resolved fashion. We show that the cyclin-Cdk1-Cks1-dependent phosphorylation of multisite targets in Saccharomyces cerevisiae is controlled by key substrate parameters including distances between phosphorylation sites, the distribution of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
177
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(191 citation statements)
references
References 58 publications
11
177
2
1
Order By: Relevance
“…In addition, this mechanism allows for greater control by opposing phosphatases and fine tuning of the signal process based on the number of phosphor- ylated sites involved. Cdk1-dependent multisite phosphorylation has been observed in several yeast species and Xenopus laevis suggesting that this mechanism could be conserved in human cells (57,(65)(66)(67). Further investigation of Cdk1-dependent multisite phosphorylation will be important to determine if the underlying mechanisms are also conserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this mechanism allows for greater control by opposing phosphatases and fine tuning of the signal process based on the number of phosphor- ylated sites involved. Cdk1-dependent multisite phosphorylation has been observed in several yeast species and Xenopus laevis suggesting that this mechanism could be conserved in human cells (57,(65)(66)(67). Further investigation of Cdk1-dependent multisite phosphorylation will be important to determine if the underlying mechanisms are also conserved.…”
Section: Discussionmentioning
confidence: 99%
“…3C), we found that 71% contained two or more regulated phosphopeptides and 46% contained three or more, suggesting that Cdk1 regulation of protein function occurs through cumulative multisite phosphorylation events. Multisite phosphorylation of Cdk substrates was previously reported in several yeast species and Xenopus laevis, and proposed to allow for differential regulation of substrate phosphorylation and function (57,(65)(66)(67).…”
Section: Quantitative Analysis Of the Phosphoproteome Of Flavopiridolmentioning
confidence: 99%
“…The metaphase phosphorylation peak is followed by rapid dephosphorylation resulting in Cnn1 enrichment to kinetochores at anaphase onset (Bock et al 2012). A Cdc28-dependent threshold triggers the Skp1-Cul1-F box (SCF)-mediated destruction of Sic1 at S phase entry (Koivomagi et al 2011(Koivomagi et al , 2013 and the Cnn1 metaphase phospho threshold may initiate phosphatase activity on S74 and surrounding residues. S74 from Cnn1 likely needs surrounding sites to be phosphorylated because the Cnn1 60-84 sequence can replace a similar Ndc80 binding motif in the Dsn1 protein, indicating S74 is not phosphorylated in that context (Malvezzi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For assignment, approximately 0.7 mM 15 N, 13 C Ash1 sample was used to acquire standard triple-resonance backbone assignment experiments and carbon-detect triple resonance experiments. Standard assignment experiments were based on sensitivity enhanced 1 H- 15 65 Additionally, CCCON-IPAP, a 3D 13 C TOCSY, was used to distinguish trans versus cis proline (32 scans, 1024 ( 13 C) × 48 ( 15 N) × 160 ( 13 C) complex data points, with 18 ppm, 36 ppm and 72 ppm as 13 C, 15 N and 13 C (TOCSY) sweep widths). 66 15 N NMR relaxation experiments acquired on a Bruker Avance 800 MHz spectrometer at 278 K using standard pulse programs (16 scans, 2048 ( 1 H) × 150 ( 15 N) complex data points).…”
Section: Saxs Data Analysismentioning
confidence: 99%
“…1 Multisite phosphorylation is dynamic 2 and it enables rapid signal integration [3][4] . Many nonlinear downstream responses [5][6][7][8][9][10] such as transcriptional regulation [11][12][13] , cell cycle control [4][5][14][15] , and cell proliferation 16 are coordinated by multisite phosphorylation of IDRs. Archetypal IDRs that undergo multisite phosphorylation include the C-terminal domain of RNA polymerase II 13 , the C-terminal tail of the epidermal growth factor receptor 13 , and sidearms of intermediate filaments in neurons 17 .…”
Section: Introductionmentioning
confidence: 99%